Optimization of a diagnostic platform for oxidation–reduction potential (ORP) measurement in human plasma. (1st January 2018) - Polson, David; Villalba, Nuria; Freeman, Kalev
ABSTRACT: Objectives: Oxidation–reduction potential (ORP) measurement can demonstrate the extent of oxidative stress in patients with severe illness and/or injury. A novel ORP diagnostic platform using disposable sensors (RedoxSYS) has been validated by comparison to mass spectrometry, but the optimal methods of sample handling for best performance of the device have not been described. Methods: We sought to optimize ORP measurement in human plasma under controlled conditions. We hypothesized that the anticoagulant, freeze–thawing, and storage duration would influence measured ORP levels. Results: The platform was sensitive to exogenous oxidation with hydrogen peroxide and reduction with ascorbic acid. Plasma anticoagulated with heparin was more sensitive to differences in ORP than plasma prepared in citrate. ORP measurements decreased slightly after a freeze–thaw cycle, but once frozen, ORP was stable for up to one month. Discussion: We confirm that ORP detects oxidative stress in plasma samples. Optimal measurement of plasma ORP requires blood collection in heparin anticoagulant tubes and immediate analysis without a freeze–thaw cycle.